Westonci.ca offers fast, accurate answers to your questions. Join our community and get the insights you need now. Get immediate and reliable answers to your questions from a community of experienced experts on our platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
Let's focus on the correct interpretation of the given equation. The given equation simplifies to:
[tex]\[ (x - 4)^2 = 9 \][/tex]
This is a classic case of the square root property. Let's solve it step by step.
1. Equation to solve:
[tex]\[ (x - 4)^2 = 9 \][/tex]
2. Apply the square root property:
When you have an equation in the form [tex]\((a)^2 = b\)[/tex], you can solve for [tex]\(a\)[/tex] by taking the square root of both sides. However, remember that taking the square root leads to two solutions, one positive and one negative.
Therefore:
[tex]\[ x - 4 = \pm\sqrt{9} \][/tex]
3. Simplify the square root:
We know that [tex]\(\sqrt{9} = 3\)[/tex]. So, the equation becomes:
[tex]\[ x - 4 = \pm 3 \][/tex]
4. Consider the two cases:
Case 1:
[tex]\[ x - 4 = 3 \][/tex]
[tex]\[ x = 4 + 3 \][/tex]
[tex]\[ x = 7 \][/tex]
Case 2:
[tex]\[ x - 4 = -3 \][/tex]
[tex]\[ x = 4 - 3 \][/tex]
[tex]\[ x = 1 \][/tex]
So, the two solutions to the equation [tex]\((x - 4)^2 = 9\)[/tex] are:
[tex]\[ x = 7 \][/tex] and [tex]\[ x = 1 \][/tex]
Conclusively, the solutions for the given equation [tex]\((x - 4)^2 = 9\)[/tex] are:
[tex]\[ x = 7 \, \text{and} \, x = 1 \][/tex]
[tex]\[ (x - 4)^2 = 9 \][/tex]
This is a classic case of the square root property. Let's solve it step by step.
1. Equation to solve:
[tex]\[ (x - 4)^2 = 9 \][/tex]
2. Apply the square root property:
When you have an equation in the form [tex]\((a)^2 = b\)[/tex], you can solve for [tex]\(a\)[/tex] by taking the square root of both sides. However, remember that taking the square root leads to two solutions, one positive and one negative.
Therefore:
[tex]\[ x - 4 = \pm\sqrt{9} \][/tex]
3. Simplify the square root:
We know that [tex]\(\sqrt{9} = 3\)[/tex]. So, the equation becomes:
[tex]\[ x - 4 = \pm 3 \][/tex]
4. Consider the two cases:
Case 1:
[tex]\[ x - 4 = 3 \][/tex]
[tex]\[ x = 4 + 3 \][/tex]
[tex]\[ x = 7 \][/tex]
Case 2:
[tex]\[ x - 4 = -3 \][/tex]
[tex]\[ x = 4 - 3 \][/tex]
[tex]\[ x = 1 \][/tex]
So, the two solutions to the equation [tex]\((x - 4)^2 = 9\)[/tex] are:
[tex]\[ x = 7 \][/tex] and [tex]\[ x = 1 \][/tex]
Conclusively, the solutions for the given equation [tex]\((x - 4)^2 = 9\)[/tex] are:
[tex]\[ x = 7 \, \text{and} \, x = 1 \][/tex]
Visit us again for up-to-date and reliable answers. We're always ready to assist you with your informational needs. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.